New, Emerging, and Threatening Plant Diseases and Crop Biosecurity - Tim Momol; Jim Marois; Bob McGovern; Pam Roberts; Gail Wisler (EDIS, 2003)
This document is Fact Sheet PP195, one of the Plant Pathology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published April 2003.